Truth-Seeking by Abduction - Niiniluoto, Ilkka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book examines the philosophical conception of abductive reasoning as developed by Charles S. Peirce, the founder of American pragmatism. It explores the historical and systematic connections of Peirce's original ideas and debates about their interpretations. Abduction is understood in a broad sense which covers the discovery and pursuit of hypotheses and inference to the best explanation. The analysis presents fresh insights into this notion of reasoning, which derives from effects to causes or from surprising observations to explanatory theories. The author outlines some logical and AI approaches to abduction as well as studies various kinds of inverse problems in astronomy, physics, medicine, biology, and human sciences to provide examples of retroductions and abductions. The discussion covers also everyday examples with the implication of this notion in detective stories, one of Peirce$1 (Bs own favorite themes. The author uses Bayesian probabilities to argue that explanatory abduction is a method of confirmation. He uses his own account of truth approximation to reformulate abduction as inference which leads to the truthlikeness of its conclusion. This allows a powerful abductive defense of scientific realism. This up-to-date survey and defense of the Peircean view of abduction may very well help researchers, students, and philosophers better understand the logic of truth-seeking.s
Preface -- Chapter 1. Peirce on Abduction -- Chapter 2. Analysis and Synthesis -- Chapter 3. Abduction and Logic -- Chapter 4. Inverse Problems -- Chapter 5. Abduction as Discovery and Pursuit -- Chapter 6. Abduction and Confirmation -- Chapter 7. Inference to the Best Explanation -- Chapter 8. Abduction and Truthlikeness -- Chapter 9. Abduction and Scientific Realism -- Bibliography -- Index.
Keywords: Epistemology; Linguistics; Mathematical logic; Logic; Philosophy and science; Epistemology; Theoretical Linguistics; Mathematical Logic and Foundations; Logic; Philosophy of Science